Effects of co-inoculation and sequential inoculation of Tetragenococcus halophilus and Zygosaccharomyces rouxii on soy sauce fermentation - Devanthi, Putu Virgina Partha; Linforth, Robert; Onyeaka, Helen; Gkatzionis, Konstantinos (Elsevier, 2018)
The use of Tetragenococcus halophilus and Zygosaccharomyces rouxii as starter cultures is essential for desirable volatiles production during moromi stage of soy sauce fermentation. In this study, the effect of simultaneous and sequential inoculation of cultures in moromi fermentation models, with respect to viability, physicochemical changes, and volatiles formation (using SPME-GC/MS) was investigated. Interestingly, an antagonism was observed as T. halophilus only proliferated (3 log increase) in the presence of Z. rouxii, while Z. rouxii growth was suppressed by 4 log in concurrence with pH increase to 7.31. Final content of reducing sugars, ethanol, acetic acid, and amino nitrogen did not differ significantly (p < 0.05) between co-inoculation and sequential inoculation. However, Z. rouxii promoted alcohols formation and produced a more complex aroma profile under suppression. According to Principal Component Analysis (PCA), the inoculation sequence (co-inoculation and sequential) has impacts on volatile compound profiles during moromi fermentation.